Evaluasi Penggunaan Dan Efektivitas Pemberian Antibiotik Pada Pasien Demam Tifoid Di Instalasi Rawat Inap RSUD Sukoharjo Pada Periode 1 Oktober - 31 Desember 2015 - Widodo, Aan Wahyu; , Dra. Nurul Mutmainah, M.Si., Apt (2017)
Typhoid fever is a systemic infection caused by Salmonella typhi that attacks small intestine with symptoms of fever that last for a week or more and accompanied by gastrointestinal disease. Typhoid fever can be treated with antibiotics. The use of appropriate and rational antibiotics provide an effective impact in terms of cost, increase clinical efficacy, minimize drug toxicity and the occurrence potential bacterial resistance. The purpose of this study is to evaluate and assess the effectiveness of antibiotics given to typhoid fever patients in the RSUD Sukoharjo on 1st October to 31st December 2015. This research was conducted by non-experimental method with retrospective data collecting. Data obtained were analyzed using descriptive statistic. The result will show accuracy of antibiotic therapy for typhoid fever patients based on the Clinical Pathways RS X (2015) to see the precision of indication that were given, the patient, medication and precision dose also the effectivity of antibiotics used in this therapy. The results of this study, the prevalence use of the following antibiotics are Cefotaxime antibiotic (50%), Ceftriaxone (15%), Cefazoline (10%), ceftazidime, ciprofloxacin and Azithromicin (2.5%) respectively and combinations of antibiotic (12.5%). The rate of precise use of antibiotic based on indication and patient is 100%, precise medicine given is 75%, and precise dose given is 35%. Evaluation results of antibiotic efficacy in typhoid fever patient is 100%.